2020
DOI: 10.1021/acs.jpcc.0c00575
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Electrical Sensing of Optically Trapped Microparticles in Motorized Liquid Flows

Abstract: Recently, electrical sensing methods for tiny objects, such as microparticles, cells, viruses, and allergen particles, have attracted much attention. However, the details of microfluidic devices have not yet been optimized because of problems with the detection frequency and the signal-to-noise (S/N) ratio. Herein, we propose applying optical forces acting on microparticles to the electrical measurement technique. First, an optical force acting on a single microparticle is quantitatively measured in the steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…The electrophoretic effect results in further modulation on the particle velocity in the orifice on the order of 10 m/s under the applied voltage of 1 V; the velocity of the electrophoresis, , is written as , where and V/m denote the electrophoretic mobility of the particle and external electric field, respectively. The is based on the Smoluchowski equation, where mV 50 , F/m, , and Pa s denote the -potential of the particle, the permittivity of vacuum, relative permittivity and viscosity of surrounding liquid, respectively. As a result is calculated as m/s, which is on the same order of that caused by the fluid drag force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophoretic effect results in further modulation on the particle velocity in the orifice on the order of 10 m/s under the applied voltage of 1 V; the velocity of the electrophoresis, , is written as , where and V/m denote the electrophoretic mobility of the particle and external electric field, respectively. The is based on the Smoluchowski equation, where mV 50 , F/m, , and Pa s denote the -potential of the particle, the permittivity of vacuum, relative permittivity and viscosity of surrounding liquid, respectively. As a result is calculated as m/s, which is on the same order of that caused by the fluid drag force.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works 48 , 49 indicated that the repetitive acquisition of the pulses improves reproducibility and resolution of the resistive pulse analysis. Furthermore, we previously performed the repetitive pulse acquisition using a single-orifice device with a standard Gaussian optical tweezer 50 , which improved the S/N ratio of the waveform. The optical manipulation helps stable translocation of the target particles; near the micro- and nanoscale structure, the complex electrohydrodynamic flow is locally induced, often preventing the particle driven by the electrophoresis from entering the sensing portion.…”
Section: Introductionmentioning
confidence: 99%
“…The present electrical measurement setup is constructed based on our previous study. 16 Single Au NP Sensing Based on the Coulter Principle. Many works about electrical sensing of small objects based on the conventional Coulter principle have already been published and reviewed, 3−5 where resistive pulses caused by the volume exclusion of target particles were often measured.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…11−14 We also previously proposed some methods for the measurement of resistive pulses, controlling the transport of target particles using optical manipulation techniques. 15,16 Such optical techniques have been used in various research fields 17−19 since the potential of optical tweezers was demonstrated by Ashkin and his coworkers. 20−23 Optical manipulation of biological cells, 24,25 biomacromolecules, 26 and small colloid particles 27,28 was used to accurately determine the positions or to form ordered structures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation